Socio-Demographic Profile of Female Victims of Vitriolage in Interior Sindh Pakistan (Medical Forum Monthly, 2024)
Object: Vitriolage is a reprehensible crime. It is an easy mean of taking revenge in our society. The most common victims of this criminal act are women. This study highlights the sociodemographic profile of such cases.Study Design: Retrospective / observational study.Place and Duration of Study: This study was conducted in the medico-legal section of Deptt. of Forensic Medicine and Toxicology, PUMHS for Women, District Shaheed Benazirabad during the period from 1st January 2013 to 31st December 2013.Material & Methods: Sixteen cases of vitriolage were studied with reference to age, literacy, socioeconomic background, marital status, occupation, relationship with offender, time of incidence, time between occurrence and medical examination, place of incidence.Results: All the cases were females, majority in age group 20-30, unmarried, uneducated, from middle class, had first degree burns and disfigurement of face. The offenders were known to victims in all the cases.Conclusion: The problem needs to be acknowledged by public at large. Individuals social issues should be resolved timely and wisely to guard against such happenings. Emotionally unstable people must be provided counseling by psychologists. The initiative taken by Peshawar High Court in the form of restriction on the sale of acid is a great attempt to minimize the risk and should be appreciated.